Antibacterial activity of zinc oxide nanoparticles against Listeria monocytogenes ATCC 7644 - Ahón-Ríos, Karen Alejandra (2022)
background: Zinc oxide nanoparticles (Np-ZnO) have different behaviors which allows its application in various areas. Objectives: To determine the minimum inhibitory concentration (MIC) of Zinc oxide nanoparticles for Listeria monocytogenes ATCC 7644. The study: Zinc oxide nanoparticles with an average size of 90nm and different concentrations of 4; 2; 1; 0,5; 0,25; 0,12; 0,06; 0,03; 0,01; 0,007 mg/mL prepared in aqueous solution were used. It was incubated at a time corresponding to generation time of the bacteria, evaluating the growth with the presence of turbidity. Findings: The MIC for Listeria monocytogenes ATCC 7644 was 0,06 mg/mL. Conclusion: The minimum inhibitory concentration (MIC) of Zinc oxide nanoparticles (Np-ZnO) with an average size of 90nm for Listeria monocytogenes ATCC 7644 was 0,06 mg/mL, enough value to significantly control the growth of for Listeria monocytogenes ATCC 7644.